Comunicación interna y desempeño laboral en los colaboradores de la Municipalidad Distrital de Saquena, 2023 - Cabezas Marin, Frank Pedro (2023)
Our present thesis has as a general objective "To determine how internal communication influences the work performance of the collaborators of the District Municipality of Saquena, 2023." It adopts a correlational descriptive approach and follows a non-experimental design. In this type of design, our main objective is to describe the situation related to our study problem without intervening or manipulating the variables. We will base ourselves solely on the observation of the variables and on the identification of the relationships that exist between them. Variables 1 and 2 are equal to 0.665** Pearson and with a bilateral sigma of 0.001, this is less than 0.05 by the general decision rule, we conclude that "There is a positive and significant relationship between internal communication and job performance in the District Municipality of Saquena, 2023.